Strategi Implementasi SIEM untuk Mengurangi Risiko terhadap Kebocoran Informasi - Anggara, Taufik Rendi (Jurnal Teknologi Terpadu, 2023)
More than 100 instances of information leakage brought on by unauthorized access occurred in 2022. This study used case studies in conjunction with system development. Early Warning Systems (EWS) are intended to give current information on event violations. When the worker goes to the console, EWS will warn and ask for verification. In Centralised Log Management (CLM), data logs were filtered with a policy-based Correlation setup approach. Network Security devices are configured for Rule-Based Correlations, and log data will be forwarded to CLM. In the case of an occurrence, logs are crucial to the inquiry. We used the CLM model to secure log data. EWS can filter harmful activity and malicious events from all current devices using this CLM. EWS will send any malicious activities or events it detects through telegram and email. Applying CLM and EWS with IT risk measurement can assist in reducing the risk of information leakage and offer quick information for breaches or incidents, according to this study. Evaluation, which lasted for two weeks, produced outcomes including less unauthorized activity, outstanding performance in the notification system that may assist in verifying access to the proper privileges for accessing the device, and simple detection of unauthorized access and file modifications, among other things.